Life on a little-known planet : dispatches from a changing world - Kolbert, Elizabeth (Crown, 2025)
"A landmark collection of Pulitzer Prize winner Elizabeth Kolbert's most important pieces about climate change and the natural world "To be a well-informed citizen of Planet Earth," Rolling Stone has advised, "you need to read Elizabeth Kolbert." From her National Magazine Award-winning series The Climate of Man to her Pulitzer Prize-winning book The Sixth Extinction, Kolbert's work has shaped the way we think about the environment in the twenty-first century. Collected in Life on a Little-Known Planet are her most influential and thought-provoking essays. An intrepid reporter and a skillful translator of scientific idees, Kolbert expertly captures the wonders of nature and paints vivid portraits of the researchers and concerned citizens working to preserve them. She takes readers all around the globe, from an island in Denmark that's succeeded in going carbon neutral, to a community in Florida that voted to give rights to waterways, to the Greenland ice sheet, which is melting in a way that has implications for everyone. We meet a biologist who believes we can talk to whales, an entomologist racing to find rare caterpillars before they disappear, and a climatologist who's considered the "father of global warming," amongst other scientists at the forefront of environmental protection. The threats to our planet that Kolbert has devoted so much of her career to exposing have only grown more serious. Now is the time to deepen our understanding of the world we are in danger of losing"-- Provided by publisher.